Effectiveness of Music Therapy in Reducing Stage Fright in Musicians: A Preventive Study - OLALLA , VERÓNICA ARROYO (Journal of Ecohumanism, 2024)
Introduction: It is common for musicians of all ages to experience social phobia and stage fright. The paper examines a number of approaches to understanding and treating this problem, emphasizing the importance of adapting strategies to suit each particular case. Methodology: The research employs a combination of documentary and field methods to address the issue of stage fright in young musicians. The study was based on an intentional sampling of 124 students, aged between 8 and 16, who attended classes designed to address stage fright during a summer camp. In order to assess the emotional state and evolution of the students, interviews, observations and practical exercises are employed during music classes. The data is subjected to analysis in order to identify patterns and to establish solutions that are tailored to the specific needs of each student. Results: Following the initial concert, the majority of students exhibited symptoms of stage fright, including palpitations, shortness of breath and stomach discomfort. This corroborated the hypothesis of the study and led to the implementation of music therapy exercises focused on relaxation, breathing and body control, as well as emotional expression. Following the concert, a notable enhancement was observed in the sample, with the participants affirming that the exercises were instrumental in regulating their nervous system. Conclusion: The results substantiate the efficacy of music therapy in mitigating stage fright in young musicians. In conclusion, the results of this study indicate that music therapy can be an effective approach for reducing stage fright in young musicians. It is of great importance to adapt treatment strategies to the individual needs of students and the educational environment to create an environment of support and understanding. It is acknowledged that the sample size and duration of the study may have been insufficient to yield conclusive results. Therefore, it is recommended that further research be conducted with larger samples and long-term follow-up to gain a more comprehensive understanding of the subject matter.